2018
DOI: 10.1016/j.ymgmr.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of maple syrup urine disease, propionic acidemia, and methylmalonic aciduria from newborn screening data

Abstract: Incidence for the branched-chain intoxication-type disorders, maple syrup urine disease, propionic acidemia and methlymalonic aciduria is dependent on the population screened. Here newborn screening results from three world regions, state screening laboratories in the United States, a region in Germany and Kuwait provides new incidence numbers. Maple syrup urine disease incidence in the United States was calculated to be 1: 220219, in South-West Germany 1: 119573 (Germany nationwide 1:177978), and in Kuwait 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 24 publications
(28 reference statements)
2
21
0
3
Order By: Relevance
“…Our findings align well with epidemiological studies published by Peng et al [67] and Chapman et al [62] after our review was performed [62, 67] and the systematic literature review by the Spanish Health Technology Assessment Agency , which was conducted with the purpose of evaluating the effectiveness of newborn screening programs [68]. However, compared to this work, our review was not restricted to screening programs, therefore, it provides a more comprehensive overview on disease epidemiology.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings align well with epidemiological studies published by Peng et al [67] and Chapman et al [62] after our review was performed [62, 67] and the systematic literature review by the Spanish Health Technology Assessment Agency , which was conducted with the purpose of evaluating the effectiveness of newborn screening programs [68]. However, compared to this work, our review was not restricted to screening programs, therefore, it provides a more comprehensive overview on disease epidemiology.…”
Section: Discussionsupporting
confidence: 94%
“…In the region of MENA, the meta-analysis results indicated higher disease frequencies for MMA and its isolated form. These results are in line with the recent findings of Chapman et al (2018) who reported a detection rate of 5.05, 1.44 and 0.18 per 100,000 newborns of isolated MMA in Kuwait, United States and South-West Germany, respectively [62].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of MSUD in the United States is estimated to be 1:200,000, though some populations have much higher incidence rates. Such populations include the Mennonite population, with a reported incidence as high as nearly 1:350; the Galician population in Spain, with an incidence of 1:52,500; and the Ashkenazi Jewish population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason could be similar to that of maple syrup disease where branched chain keto acid dehydrogenase dysfunction results in elevation of BCAA in serum and excretion of the same in urine. 21 The estimation of BCAA in serum requires a well equipped laboratory with much more expensive and advanced tests like HPLC, Nuclear magnetic resonance (NMR) spectroscopy 11 , Liquid chromatography-Mass spectrometry 12 . Qualitative estimation of leucine in urine by TLC is a simple and cheaper technique which could be an alternative for estimation of serum leucine.…”
Section: Discussionmentioning
confidence: 99%